EFEK MODERASI VARIABEL RISIKO PASAR HARGA KOMODITAS AYAM, TELUR, JAGUNG, DAN GANDUM PADA PENGARUH RASIO PROFITABILTAS DAN RASIO LEVERAGE TERHADAP NILAI PERUSAHAAN PAKAN TERNAK DI INDONESIA PERIODE TAHUN 2016 – 2020 - Sastra, Denny Putra Danuh; Lumbantobing, Rudolf (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The purpose of this study was to examine the effect of profitability ratios and leverage ratios on firm value, as well as the moderating effect of commodity prices on these ratio variables. The sample taken is all animal feed companies listed on the Indonesia Stock Exchange (IDX) with the data selected for the year 2016 – 2020. The analysis is based on data from 4 companies and the data taken is sourced from financial reports. The research was conducted using descriptive statistical analysis with multiple regression analysis model. The results of the study indicate that the profitability ratios represented by ROA, ROE and NPM have a positive and significant effect on firm value represented by EPS, PBV and stock prices. The leverage ratio represented by LT Debt, ST Debt, DER and DAR has a negative and significant effect on firm value. Further research shows that the price of chicken moderates the profitability ratios positively and significantly on firm value. Egg prices moderate the profitability ratios negatively and significantly on firm value. For corn prices and wheat prices did not significantly moderate the ratio of profitability to firm value. Likewise for chicken prices, egg prices, corn prices and wheat prices did not significantly moderate the leverage ratio to firm value. From the results of this study, it can be concluded that for investors who want to invest in shares in animal feed companies, it is better to look at the profitability ratio indicator because it will have a positive impact on stock returns. Meanwhile, with the greater the leverage ratio, the animal feed company must be careful in managing the company's financing that comes from debt because it will have an impact on the value of the company. In addition, commodity prices that have an influence are chicken prices and egg prices, so in making a decision to see the effect on company value, it is necessary to look at the prices of these two commodities.